Interplay Between Astroglial Endocannabinoid System and the Cognitive Dysfunction in Alzheimer's Disease - Rapaka, D; Adiukwu, P C; Challa, S R; Bitra, V R (Physiological research, 2023)
Cannabinoid CB1 receptors have been shown to regulate wide array of functions ranging from homeostasis to the cognitive functioning but recent data support the hypothesis that astrocytes also operate as a mediator of synaptic plasticity and contribute to cognition and learning. The receptor heterogeneity plays a key role in understanding the molecular mechanisms underlying these processes. Despite the fact that the majority of CB1 receptors act on neurons, studies have revealed that cannabinoids have direct control over astrocytes, including energy generation and neuroprotection. The tripartite synapse connects astrocytes to neurons and allows them to interact with one another and the astrocytes are key players in synaptic plasticity, which is associated with cognitive functions. This review focuses on our growing understanding of the intricate functions of astroglial CB1 that underpin physiological brain function, and in Alzheimer's disease.
Keywords: kognitivní dysfunkce; Astrocytes; Alzheimerova nemoc; Alzheimer Disease; lidé; astrocyty; endokanabinoidy; Cognitive Dysfunction; neuroplasticita; neurony; Neuronal Plasticity; Humans; Neurons; Endocannabinoids